Analysis of volatile compounds in five jackfruit (Artocarpus heterophyllus L.) cultivars using solid-phase microextraction (SPME) and gas chromatography-time-of-flight mass spectrometry (GC-TOFMS) - Ong, B. T.; Sheikh Abdul Hamid, Nazimah; Tan, Chin Ping; Mirhosseini, Seyed Hamed; Osman, Azizah; Mat Hashim, Dzulkifly; Rahmat Ali, Gulam Rusul (Elsevier, 2008)
In the present study, the jackfruit volatile compounds were established using solid-phase microextraction (SPME) and gas chromatography-time-of-flight mass spectrometry (GC-TOFMS). Qualitative and quantitative analyses were carried out using 5 g samples with divinylbenzene/carboxen/polydimethylsiloxane (DVB/CAR/PDMS) fibre at 30 °C for 10 min. Rapid spectral acquisition rate of 10 spectra/s by the GC-TOFMS permitted identification and quantification of compounds having chromatographic peak widths of only a fraction of second. For SPME-GC-TOFMS analysis, the total time was approximately 18 min. Thirty-seven compounds were identified from five jackfruit cultivars. The main jackfruit volatile compounds were: ethyl isovalerate, 3-methylbutyl acetate, 1-butanol, propyl isovalerate, isobutyl isovalerate, 2-methylbutanol, and butyl isovalerate. These compounds were consistently present in all the five cultivars and this suggests the compounds contributed to the sweet and fruity note of jackfruit. Principal component analysis (PCA) applied to the data, differentiated the five jackfruit cultivars according to their unique flavour compounds and explained 88% of the total variance.